2017
DOI: 10.1002/ijgo.12297
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prenatal corticosteroid use in spontaneous preterm labor in the Brazilian Multicenter Study on Preterm Birth (EMIP)

Abstract: Preterm labor and late preterm delivery were associated with worse neonatal outcomes following prenatal corticosteroids. This could reflect a sub-optimal interval between administration and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Around 65% of sPTB before 34 weeks and 30% of late sPTB used ACS. The EMIP study, a multicentre cross-sectional study in 20 referral maternities in Brazil, showed that ACS was used in 54.0% of sPTB before 34 weeks and in 14.0% of late sPTB 27 . In accordance with the evidence-based recommendation for using ACS between 34 and 36 weeks raised by ALPS study 28 in 2016 and by 2017 Cochrane Systematic review 23 , an increase in the use of ACS can be observed between both Brazilian studies, EMIP (2011-2012) and Preterm SAMBA (2015-2018).…”
Section: Discussionmentioning
confidence: 99%
“…Around 65% of sPTB before 34 weeks and 30% of late sPTB used ACS. The EMIP study, a multicentre cross-sectional study in 20 referral maternities in Brazil, showed that ACS was used in 54.0% of sPTB before 34 weeks and in 14.0% of late sPTB 27 . In accordance with the evidence-based recommendation for using ACS between 34 and 36 weeks raised by ALPS study 28 in 2016 and by 2017 Cochrane Systematic review 23 , an increase in the use of ACS can be observed between both Brazilian studies, EMIP (2011-2012) and Preterm SAMBA (2015-2018).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics may explain the increased use of antenatal corticosteroids in this group. The use of corticosteroids was previously evaluated in EMIP ( 17 ) and the results showed better outcomes among those who received this intervention before 34 weeks of preterm labor. In hypertensive disorders in pregnancy, mostly preeclampsia, the fetuses are exposed to oxidative stress, chronic hypoxia, and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…12 Among the women with preterm birth with gestational age less than 34 weeks, almost three-fourths received a corticosteroid, which was higher than the finding of a Brazilian Multicenter Study on Preterm Birth. 22 Three-fourths of the women in our study received a corticosteroid with the same dose and route as recommended by the American College of Obstetricians and Gynecologists. 23 A low proportion of women received a tocolytic in our study because most of the preterm women had gestational age >34 weeks or other indications for inducing preterm birth.…”
Section: Discussionmentioning
confidence: 99%